American silence - Papanikolas, Zeese (Lincoln : University of Nebraska Press, 2007)
In American Silence, a complement to his previous study Trickster in the Land of Dreams, Zeese Papanikolas investigates a number of significant American cultural artifacts and the lives of their makers. For Papanikolas, both the private failures and public successes of Clarence King, Henry Adams, Gertrude Stein, Ernest Hemingway, Raymond Chandler, and Hank Williams resonate with silences.
Overture : the unpaintable West -- The inner geology of Clarence King -- Henry Adams at the fair -- The cruelty of seeing -- Some versions of the pastoral -- Sublime America -- Lonesome America.
Includes bibliographical references (pages 191-212) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States -- Civilization; West (U.S.) -- Civilization; National characteristics, American; United States -- Intellectual life; Silence in literature; Silence in art; Failure (Psychology) -- Case studies; United States -- Biography -- Anecdotes; Authors, American -- Biography -- Anecdotes; Artists -- United States -- Biography -- Anecdotes; États-Unis -- Civilisation; États-Unis -- Vie intellectuelle; Silence dans la littérature.; Silence dans l'art.; Échec -- Études de cas; États-Unis -- Biographies -- Anecdotes; Écrivains américains -- Biographies -- Anecdotes; Artistes -- États-Unis -- Biographies -- Anecdotes; États-Unis (Ouest) -- Civilisation; HISTORY; HISTORY -- United States -- 20th Century; Artists; Authors, American; Civilization; Failure (Psychology); Intellectual life; National characteristics, American; Silence in art; Silence in literature; United States; West United States; Nationalcharakter; Literatur; Kunst; USA; Electronic books; Biography; Biographies; Anecdotes; Case studies; Biographies; Biographies